HELMECZY MIHÁLY, A JELENKOR LAPSZERKESZTŐJE KÖZÉLETI ÉS SZAKMAI HÁTTERÉNEK VIZSGÁLATA A KORABELI FORRÁSOK TÜKRÉBEN - Dr. Döbör, András (Közép-Európai Közlemények, 2019)
In Hungary, at the end of the 1820s, a new political program appeared as Count István Széchenyi came on the scene, which wanted to serve the civil transformation with the help of the national public instead of the county-level scope of the policy of feudal grievances. Széchenyi studied the role of the public in the emergence of modern political debate primarily during his trip to England and after returning home he lobbied for the creation of a political newspaper. After two years of wrangling for the licenses, „Jelenkor. Politikai tekintetben a’ két haza ‘s külföld hírleveleiből” (Our Times. In Political Point of View from the Newsletters of the Two Nations and Abroad”), edited by Mihály Helmeczy. Originally, Kisfaludy Károly, a member of the Auróra Magazine, highly regarded by Széchenyi, was marked out for the task to unite new literary efforts and political reforms in the new political newspaper. But Kisfaludy died in a serious illness on November 21, 1830, so licensing had to start with a new man. As a result of Széchenyi’s habit to make quick moves, he suggested Mihály Helmeczy, who belonged also to the Auróra circle, to be the successor, and he got through with his intention. Finally, on 11 March, 1831, the Court granted Mihály Helmeczy the license, the first issue of Jelenkor was published on January 4, 1832, and edited by Helmeczy until 1848 when the newspaper was ceased. Széchenyi stood behind the paper, but he was not involved in editing the newspaper, he only published occasionally in the supplementary newspaper. Jelenkor symbolizes the beginning of a new era of the Hungarian press history with its typography. A new relationship between the demand of the audience and the political newspaper had been marked by an unprecedented number of copies: over 3,000 in 1835, and over 4,000 subscribers in 1837. In my study, I present the influence of Széchenyi on the newspaper, the selection process of the editor, and Helmeczy’s public and professional background, which eventually made him suitable for the long-term operation of the newspaper.